2015
DOI: 10.1021/acsami.5b08764
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Lithography of 3D Nanocomposite Piezoelectric Scaffolds for Cell Stimulation

Abstract: In this letter, we report on the fabrication, the characterization, and the in vitro testing of structures suitable for cell culturing, prepared through two-photon polymerization of a nanocomposite resist. More in details, commercially available Ormocomp has been doped with piezoelectric barium titanate nanoparticles, and bioinspired 3D structures resembling trabeculae of sponge bone have been fabricated. After an extensive characterization, preliminary in vitro testing demonstrated that both the topographical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 30 publications
(56 reference statements)
0
85
0
Order By: Relevance
“…With the ability of generating electric potential upon mechanical stress, piezoelectric materials can perform different tasks in histological applications such as cells stimulation and differentiation . Marino et al realized 3D structures bioinspired to the shape of bone trabeculae via 2PP employing OrmoComp resist containing 10% piezoelectric barium titanate NPs (BTNPs) and demonstrated the possibility of osteogenic differentiation of SaOS‐2 osteoblast‐like cells under ultrasonic stimulation ( Figure a–e) . Piezoelectricity of the composite was assessed through piezoresponse force microscopy (PFM), confirming that material is characterized by a piezoelectric coefficient d 33 about one order of magnitude higher compared to that of the plain Ormocomp without barium titanate NPs.…”
Section: Nanocompositesmentioning
confidence: 79%
“…With the ability of generating electric potential upon mechanical stress, piezoelectric materials can perform different tasks in histological applications such as cells stimulation and differentiation . Marino et al realized 3D structures bioinspired to the shape of bone trabeculae via 2PP employing OrmoComp resist containing 10% piezoelectric barium titanate NPs (BTNPs) and demonstrated the possibility of osteogenic differentiation of SaOS‐2 osteoblast‐like cells under ultrasonic stimulation ( Figure a–e) . Piezoelectricity of the composite was assessed through piezoresponse force microscopy (PFM), confirming that material is characterized by a piezoelectric coefficient d 33 about one order of magnitude higher compared to that of the plain Ormocomp without barium titanate NPs.…”
Section: Nanocompositesmentioning
confidence: 79%
“…Marino et al . have functionalized commercially available Ormocomp® photopolymer with barium titanate nanoparticles, endowing it with piezoelectric properties . Ovsianikov et al .…”
Section: Introductionmentioning
confidence: 99%
“…15 Marino et al have functionalized commercially available Ormocomp ® photopolymer with barium titanate nanoparticles, endowing it with piezoelectric properties. 16 Ovsianikov et al have demonstrated the possibility of encapsulating living cells inside photopolymerizable materials and keeping them viable after structure formation. 17 The chemical, mechanical and topographical properties of materials can influence cellular processes.…”
Section: Introductionmentioning
confidence: 99%
“…A possible excitation mechanism can be envisioned by doping the materials with piezoelectric nanoparticles [36] or carbon nanotubes [37] to allow for electrical or optical [38] excitation. As the pore size in the designed lattice materials corresponds to a typical biological cell size (10-100 μm), our metamaterial microlattices can find applications in technologies for cell-based assays, cell surgery, and cellular-scale microbalances.…”
Section: Discussionmentioning
confidence: 99%